Reforming the Tax Mix in Canada - Bev Dahlby (The School of Public Policy Publications, 2012)
Periodically, tax systems need major reforms to remove the “barnacles” that accumulate under the short-term pressures of political expediency and to adapt to the long-term forces of technological and economic change.  The current fiscal and economic problems that confront the provinces require an assessment of much-needed reforms. Raising tax revenue imposes large costs on our society, not only because of the administration and compliance costs of collecting taxes, but because taxes distort economic decisions in the private sector. This is especially true of provincial corporate income taxes. Taxing highly mobile corporate capital and corporate profits encourages firms to shift their investments and profits across provincial and international boundaries. The provinces would enjoy significant boosts to economic growth and efficiency gains by enacting a revenue-neutral switch from corporate to sales or personal income taxes. For Alberta, such a shift would yield up to $40 per dollar of tax revenue shifted from corporate to personal income taxes; for fiscal year 2011-12, this would amount to a percapita welfare gain of roughly $19,000. Other options for tax reform are also discussed in this paper, including the adoption of a penny tax to the GST to fund infrastructure spending by municipalities. However, we think this would saddle the private sector with significant compliance costs and create major economic distortions between neighbouring municipalities by creating an incentive to shop where the penny tax proposal was not adopted. In surveying the most pressing tax reform issues facing Canada, we offer policymakers a firm basis for coming to grips with them, so they can treat tax dollars with the care and foresight Canadians expect.